Analysis of glucose carbon fluxes in continuous cultures of Bacillus thuringiensis - Mignone, Carlos Fernando (1996)
The glucose carbon fluxes in continuous cultures of Bacillus thuringiensis grown in a complex medium have been studied as a function of the growth rate. The results are discussed in the light of a growth model. From reduced nicotinamide adenine dinucleotide (NADH) and carbon balances it was determined that the fraction of glucose consumed for biomass synthesis decreased with the growth rate, while the glucose flux through the tricarboxylic acid (TCA) cycle diminished after a threshold value of D=0.34 h-1, where D=dilution rate. At the highest growth rate tested, glucose was used almost exclusively as the energy source, via fermentative pathways, which indicates that the yeast extract was used as the carbon source. The specific rate of oxygen consumption increased with growth even after the beginning of the accumulation of acids, indicating that the respiratory chain was not saturated. The results suggest that there is a mismatch between glycolysis and TCA cycle capacity, depending on the growth rate. Furthermore, values of (P/O) ratio and mATP are presented, where (P/O) is mole of ATP formed per gram atom oxygen consumed by the respiratory chains and mATP is the maintenance requirement for ATP.